Economic importance of the Belgian ports: Flemish maritime ports, Liège port complex and the port of Brussels – Report 2012 - Claude Mathys (National Bank of Belgium, 2014)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Ostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centers facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels for the period 2007 - 2012, with an emphasis on 2012. Focusing on the three major variables of value added, employment and investment, the report also provides some information based on the social balance sheet and an overview of the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. As a result of the underlying calculation method the changes of indirect employment and indirect value added can differ from one another. (...) Following the 2009 decline and the improvement in 2011, maritime traffic in the Flemish ports began falling again in 2012. That applies to all the Flemish ports. Value added was rising in the maritime cluster of the Flemish ports and falling in the non-maritime cluster where trade and industry were in decline. Direct value added has risen in the ports of Antwerp and Ostend whereas it has fallen in the ports of Zeebrugge and Ghent. Conversely, direct employment was expanding in both clusters in the Flemish ports viewed as a whole and in each port taken individually. The decline in investment in the Flemish ports continued in 2012. That trend is evident in all the Flemish ports except the port of Ostend where investment was maintained in 2012. The volume of cargo handled in the port of Liège decreased in 2012. Direct value added and employment contracted in both clusters. The steel giant ArcelorMittal had idled two blast furnaces at the site in Liege. Investment increased in both clusters in the Liège port complex. The volume of cargo handled at the port of Brussels declined in 2012. Value added and employment in the maritime cluster fell but rose in the non-maritime cluster. The drop in investment recorded since 2009 continued throughout 2012, albeit at a slowing pace. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2012.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport; intermodality; public investments